Measurement and Evaluation Management for Basic Education of Educational Service Area Office - Kanchai, Siranee; Jonkonklang, Sirinat; Pilanthananond, Nataya (Ratchaphruek Journal, 2021)
This research was a documentary research which aimed to study the management of the measurement and evaluation in education for the Basic Education of Education Service Area Office. The samples were purposive sampling from 6 states of education service area in the United States which were synthesized from their websites. The research was divided into 3 phases; 1) To synthesis measurement and evaluation management tasks; 2) To evaluate the measurement and evaluation management tasks; and 3) To develop and create measurement and evaluation management activities. Research tools were the data record form, the draft of evaluation tasks of basics education, and the suitability assessment questionnaire of this draft. Data were analyzed by the frequency and the percentage. The research results found that in the United States, measurement and evaluation is related to 3 departments including national department, state department and school district department. Using measurement and evaluation task towards normal students, students with disabilities and special needs and bilingual students. There was a measurement and evaluation management committee. The results are reported to school districts, schools, students and parents. The results were implemented for monitoring student plan, curriculum revision, and teachers and students’ development. in Thailand. The results found that the education service area should evaluate for all types of students, and all classes in every academic year, in the main subjects: Thai Language, Mathematics, Science, and English Language with a variety of methods. Performance scores of students with disabilities should be included. It should have a responsible committee. The results should be reported to schools, students, and parents. The results were implemented for developing teachers, students, and innovation of educational evaluation area.